The genera Acaromantis and Simognathus (Simognathinae, Halacaridae) on the north coast of São Paulo State, Brazil - Pepato, A. R.; Tiago, C. G. (Zootaxa, 2004)
This is the first record of the subfamily Simognathinae for the Brazilian coast. Two new species are described, Acaromantis vespucioi sp. nov. and Simognathus euphractus sp. nov. The description of Simognathus fuscus Viets, 1936 is extended with the inclusion of juveniles description.